Additions to the reported Elimaea species (Orthoptera: Phaneropteridae: Phaneropterinae) from India - Nagar, Rajendra; Mal, Jhabar; Swaminathan, R. (Zootaxa, 2014)
The genus Elimaea (Tettigoniidae: Phaneropterinae) has reportedly been represented in India by eight species. Four species in addition to the existing checklist are described, which were earlier reported from the Malay Peninsula, based on the teeth on stridulatory file (on the underside of male left tegmen) and modifications of the gonangulum of the ovipositor. The morphometric variations in the reported species have been given, which include E. securigera, E. subcarinata, E. thaii, E. chloris, E. nautica and E. subcarinata sp. nov. (that differs from E. subcarinata).